2012
DOI: 10.17221/147/2011-cjgpb
|View full text |Cite
|
Sign up to set email alerts
|

Transgene coding of a key enzyme of the glycolytic pathway helps to decrease sugar content in potato tubers

Abstract: Cold-stored potato tubers gradually accumulate reducing sugars. A proposed reason is a cold-induced blocking of glycolysis. The introduction and expression of the bacterial gene Lbpfk coding for cold-tolerant phosphofructokinase might counteract this effect. We have recently introduced this gene into several Czech potato cultivars. The obtained transgenic lines were then tested for three years in field trials. In 17 transgenic lines derived from two of the cultivars we have investigated the accumulation of red… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2015
2015
2017
2017

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 8 publications
0
3
0
Order By: Relevance
“…Thus, the glycolysis pathway is inhibited in tubers stored at low temperatures, resulting in the accumulation of sucrose and eventually an increase in the RS content. The bacterial phosphofructokinase gene Lbpfk was introduced into several potato cultivars, and the RS content in transgenic tubers was lower than in controls after both 2 and 4 months of cold storage . Two other genes encoding glyceraldehyde 3‐phosphate dehydrogenase ( StGAPC ) and Enolase ( StEnolase ) were cloned from S. berthaultii , and both genes were up‐regulated in cold‐stored tubers.…”
Section: Hexogenesis Glycolysis and Anaerobic Respiration In Potatomentioning
confidence: 99%
“…Thus, the glycolysis pathway is inhibited in tubers stored at low temperatures, resulting in the accumulation of sucrose and eventually an increase in the RS content. The bacterial phosphofructokinase gene Lbpfk was introduced into several potato cultivars, and the RS content in transgenic tubers was lower than in controls after both 2 and 4 months of cold storage . Two other genes encoding glyceraldehyde 3‐phosphate dehydrogenase ( StGAPC ) and Enolase ( StEnolase ) were cloned from S. berthaultii , and both genes were up‐regulated in cold‐stored tubers.…”
Section: Hexogenesis Glycolysis and Anaerobic Respiration In Potatomentioning
confidence: 99%
“…The group included: Arabidopsis thaliana, the most important model organism used in plant biology and genetics as well as in the study of plant-pathogen interactions; Nicotiana benthamiana, a popular model species in plant virology and the study of RNA silencing; soybean ( Glycine max , cv Jack), the most important legume crop and which is also used in our laboratory to study its potential to express and accumulate pharmaceutically valuable proteins such as vaccines and antibodies in its seeds [ 14 , 15 ]; potato ( Solanum tuberosum , cv. Kamýk), an important food crop which is used in our laboratory to study sugar metabolism and virus resistance [ 16 - 18 ]; and oilseed rape ( Brassica napus , cv Columbus), an important oilseed crop which is used in our lab in studies of plant-pathogen interactions [ 19 , 20 ]. In our study we demonstrated that LED tubes provide a viable alternative to current fluorescent tubes.…”
Section: Introductionmentioning
confidence: 99%
“…Early studies showed that the exogenous expression of PFK, encoding a key enzyme of the glycolysis pathway, reduced the sugar content of potato tubers. 73 For higher organisms, there is a positive correlation between the respiration rate and the enzyme activity in the citrate cycle. [74][75][76] In this study, we assessed the relationship between 6 key genes in these two pathways, including DLAT, PDHB, CS and SDHA, PFK and PGK, as well as the polysaccharide content ( Fig.…”
Section: Discussionmentioning
confidence: 99%